2014
DOI: 10.1002/2014gl062409
|View full text |Cite
|
Sign up to set email alerts
|

Carbon cycle extremes during the 21st century in CMIP5 models: Future evolution and attribution to climatic drivers

Abstract: Citation:Zscheischler, J., M. Reichstein, J. von Buttlar, M. Mu, J. T. Randerson, and M. D. Mahecha (2014), Carbon cycle extremes during the 21st century in CMIP5 models: Future evolution and attribution to climatic drivers, Geophys. Res. Lett., 41, 8853-8861, doi:10.1002 Abstract Climate extremes such as droughts and heat waves affect terrestrial ecosystems and may alter local carbon budgets. However, it still remains uncertain to what degree extreme impacts in the carbon cycle influence the carbon cycle-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 59 publications
3
40
1
Order By: Relevance
“…Several studies have found a lower drought sensitivity of R eco compared to GPP (Ciais et al, 2005;Schwalm et al, 2010Schwalm et al, , 2012Rambal et al, 2014;Zscheischler et al, 2014d) whereas we observed comparable or even slightly greater reductions NEP is the sum of the opposing fluxes of GPP and R eco and hence, the direction and amplitude of its change is always determined by the sum of the extreme event impacts on the gross fluxes. For heat extremes, the general increase in R eco adds 5 to slight decreases (or no change) of GPP, leading to a generally reduced rate of net carbon uptake.…”
contrasting
confidence: 50%
“…Several studies have found a lower drought sensitivity of R eco compared to GPP (Ciais et al, 2005;Schwalm et al, 2010Schwalm et al, , 2012Rambal et al, 2014;Zscheischler et al, 2014d) whereas we observed comparable or even slightly greater reductions NEP is the sum of the opposing fluxes of GPP and R eco and hence, the direction and amplitude of its change is always determined by the sum of the extreme event impacts on the gross fluxes. For heat extremes, the general increase in R eco adds 5 to slight decreases (or no change) of GPP, leading to a generally reduced rate of net carbon uptake.…”
contrasting
confidence: 50%
“…To our knowledge, only a single experiment has so far addressed the consequence of combined eCO 2 and elevated temperature on the ecosystem C budget (39) and found that these combined treatments increased C loss (in one of the four years of study), a result in contradiction to model simulations (40,41). The most notable effect in that experiment was the increased loss of C under elevated CO 2 (through increased heterotrophic soil respiration) in two of the four years.…”
Section: Resultsmentioning
confidence: 88%
“…Continued growth modeled through CO 2 fertilization and increased water-use efficiency Cox et al 2013, Zscheischler et al 2014, Sitch et al 2015 PJ 9…”
Section: Observationsmentioning
confidence: 99%
“…There is abundant and strong evidence demonstrating that CO 2 fertilization and associated effects on water-use efficiency are large globally, including v www.esajournals.org substantial increases in water-use efficiency (Leakey 2009, Frank et al 2015a, increased tree growth and NPP (Martı-nez-Vilalta et al 2008, Pan et al 2013, widespread woody plant expansion in dryland ecosystems (Buitenwerf et al 2012, Fensholt et al 2012, Poulter et al 2014, and an overall ''greening'' observed in many regions (Jong et al 2012, Donohue et al 2013, Ahlströ m et al 2015. Thus, with further enrichment of atmospheric CO 2 concentrations at a global scale, forests are projected to continue to grow with enhanced water-use efficiency into the future (Cox et al 2013, Zscheischler et al 2014, Sitch et al 2015, which will constrain the overall importance of tree mortality from hotter drought. Greater vulnerability evidence (Table 2).…”
Section: Co 2 Fertilization and Wuementioning
confidence: 99%